2020
DOI: 10.4236/jbm.2020.88011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Golden Proportion in Patients Visiting the Oral Health Directorate of the Komfo Anokye Teaching Hospital, Kumasi

Abstract: Background: Aesthetics is a primary consideration for patients seeking dental treatment. The size and shape of the maxillary anterior teeth have significant effects not only on the dental aesthetics, but also on the complete facial aesthetics of a person. To satisfy this expressed need, the "Golden Proportion" is a numerical value that is used as a rule in achieving dental aesthetics. In the last two decades, several studies have questioned the application of this rule in dentistry. Aim: The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The formation of a geometric relationship in anterior teeth of maxilla is essential in order to make an esthetically acceptable restoration. It would be convenient and beneficial if statistically reliable relationships are created, to support teeth proportion theories [ 16 ]. In this regard, most analysis is carried out on photographs and dental casts widely; however, attempts have been made by several researchers to minimize the photographic magnification error [ 7 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of a geometric relationship in anterior teeth of maxilla is essential in order to make an esthetically acceptable restoration. It would be convenient and beneficial if statistically reliable relationships are created, to support teeth proportion theories [ 16 ]. In this regard, most analysis is carried out on photographs and dental casts widely; however, attempts have been made by several researchers to minimize the photographic magnification error [ 7 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be convenient and beneficial if statistically reliable relationships are created, to support teeth proportion theories [ 16 ]. In this regard, most analysis is carried out on photographs and dental casts widely; however, attempts have been made by several researchers to minimize the photographic magnification error [ 7 , 16 , 17 ]. In this study, W.H Ward concept was used to avoid magnification error by figuring a conversion factor, which was derived by dividing dimensions of cast teeth by the image dimension [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in our study compared to the study of Sadrhaghighi et al 19 lies in the evaluation of the effects on smile aesthetics of changing the golden ratio of the central incisor teeth along with the lateral incisors. In a study by Amuasi et al 20 in which the presence of the golden ratio was investigated in terms of the width of the upper anterior teeth, it was suggested that the value obtained was different from the accepted golden ratio value and the golden ratio rule should definitely not be applied in restoring the anterior teeth of patients. Contrary to that study, we concluded that the golden ratio is a criterion that should be evaluated while designing a smile.…”
Section: Discussionmentioning
confidence: 98%